Thrombin cleavage of the hepatitis E virus polyprotein at multiple conserved locations is required for genome replication. - Danielle M Pierce; Frazer J T Buchanan; Fraser L Macrae; Jake T Mills; Abigail Cox; Khadijah M Abualsaoud; Joseph C Ward; Robert A S Ariëns; Mark Harris; Nicola J Stonehouse; Morgan R Herod (PLoS Pathogens)
The genomes of positive-sense RNA viruses encode polyproteins that are essential for mediating viral replication. These viral polyproteins must undergo proteolysis (also termed polyprotein processing) to generate functional protein units. This proteolysis can be performed by virally-encoded proteases as well as host cellular proteases, and is generally believed to be a key step in regulating viral replication. Hepatitis E virus (HEV) is a leading cause of acute viral hepatitis. The positive-sense RNA genome is translated to generate a polyprotein, termed pORF1, which is necessary and sufficient for viral genome replication. However, the mechanism of polyprotein processing in HEV remains to be determined. In this study, we aimed to understand processing of this polyprotein and its role in viral replication using a combination of in vitro translation experiments and HEV sub-genomic replicons. Our data suggest no evidence for a virally-encoded protease or auto-proteolytic activity, as in vitro translation predominantly generates unprocessed viral polyprotein precursors. However, seven cleavage sites within the polyprotein (suggested by bioinformatic analysis) are susceptible to the host cellular protease, thrombin. Using two sub-genomic replicon systems, we demonstrate that mutagenesis of these sites prevents replication, as does pharmacological inhibition of serine proteases including thrombin. Overall, our data supports a model where HEV uses host proteases to support replication and could have evolved to be independent of a virally-encoded protease for polyprotein processing.